PELAKSANAAN PENGEMBANGAN INFRASTRUKTUR AIR BERSIH DI KABUPATEN LINGGA TAHUN 2017-2018 - Savitri, Nadia Bella; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Lingga regency is an area that has a lot of water sources from water springs, wathershed, and raw water. However the need clean water for community in Lingga regency has not been fulfilled because water supplies are uneven. Community’s need will continue to increase clean water. The condition of water container does not fit the needs of clean water. Then, the authors see the implementation of clean water infrastructure development in Lingga Regency and the inhibitory factor of implementing clean water infrastructure development of in lingga regency in 2017-2018.The purpose of this study is to describe how local government in giving authority to the PUPRPKP Service and to give authority to PDAM and what are the factors that influence these authorities by using the theory of authority and focus on accountability criteria. This study used a qualitative approach with descriptive methods. In collecting data, the writer used interview and documentation techniques. The results of this study are the implementation of clean water infrastructure development in Lingga regency based on the deconcentration principle, the Department of PUPRPKP Lingga was given authority that is the field of copyrighted work and water resources to develop clean water by making physical buildings to accommodate clean water and cooperation with BWS IV Province of Kepulauan Riau as a water resource manager that is a working unit the Ministry of public work & housing and PDAM as a clean water service provider to the community and have the authority to find a water source. Pipeline system is an activity undertaken by PDAM while non pipeline activity undertaken by community relate to the development of clean water in the village. The inhibitory factor in implementing the development of clean water infrastructure in Lingga Regency is limited budget, and still dependent on local government then the limited workforce and water sources are far from reach. Keywords: Accountability, Administration, Law, Politics